SUGGESTIONS FOR IMPROVEMENTS TO SPORE - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Tezoh Lawrence Chialefack, Tombel, Cameroon: 'Is it not possible to advertise the courses and conferences about a year before time? I am saying this because most of the courses are very interesting to us but the time is usually too short to prepare...